Contingent factors affecting network learning - Peters, Linda D.; Pressey, Andrew D.; Johnston, Wesley J. (Elsevier, 2016)
To increase understanding of the impact of individuals on organizational learning processes, this paper explores the impact of individual cognition and action on the absorptive capacity process of the wider network. In particular this study shows how contingent factors such as social integration mechanisms and power relationships influence how network members engage in, and benefit from, learning. The use of cognitive consistency and sensemaking theory enables examination of how these contingent factors influence the learning processes of two construction industry design teams embedded within more permanent home-organizational structures. A number of practical ways arise by which firms can facilitate organizational learning through their interactions with network partners. Enhancement of learning in and between organizations occurs when members are cognizant of the means by which they connect within a network to create shared meanings, and the way in which they forge ties and share expertise in the learning process they engage in.